Removal of selected polycyclic aromatic hydrocarbons using Phragmites and Vetiver in horizontal sub –surface flow constructed wetland - Ali, Rabia Daw (2020)
The research and investigation on the removal of polycyclic aromatic hydrocarbons (PAHs) with high concentration (10000μg/L) in constructed wetlands under field conditions has not been explored prior to this. Hence, in this study, Horizontal Subsurface Flow Constructed Wetland (HSFCWs) was used to remove three polycyclic aromatic hydrocarbons. The synthetic PAHs that were used in the experiments include Phenanthrene, Pyrene, and Benzo [a]Pyrene in percentages that reflected their actual contents in the industrial wastewater. The CWs sustainable treatment technique incorporates two plants namely Phragmites Karka (Phragmites) and Vetiver Zizanioides (Vetiver) where they were tested for their ability in PAHs tolerance and uptake in pot experiments for 20 days using two different concentrations (2500 and 10000μg/L). Then, it was followed by treatment of high PAHs concentration (10000μg/L) using eight Horizontal Subsurface Flow Constructed Wetland (HSFCWs), each with dimensions of (length=90cm x width=30cm x depth=50cm) and planted with Phragmites and Vetiver. While, the other twelve constructed wetlands were smaller in size (length = 45cm, width = 15cm and height = 30cm) and were used mainly to replace plants in the big CWs after sampling. The experiments on the CWs were conducted to measure plant growth, PAHs concentration in plants, PAHs removal efficiency, accumulation of PAHs in the soil of CW, and lipid effect on PAHs accumulation during sampling days according to a predetermined pattern (7, 14, 28, 42, and 72 days). The quantitative analysis of PAHs concentration was conducted by GC-FID. The mass balance technique was conducted to determine the distribution pathways of PAHs in HSFCWs. The effect of PAHs on the surface structure of different parts of Phragmites and Vetiver was investigated by using scanning microscopy. The capacity of the HSFCWs to address the wastewater contaminated with PAHs was modelled by using multiple regression stepwise method. The results revealed that the growth parameter was significantly different among the two plants. The highest concentrations of three PAHs were found to be in Phragmites shoot and root system with 229μg/g and 192μg/g, for Phenanthrene, 69μg/g and 59μg/g for Pyrene, and 25μg/g and 20μg/g for Benzo [a]Pyrene respectively. While the greatest concentrations of the same compounds in the Vetiver shoot and root systems were 88μg/g and 64μg/g for Phenanthrene, 63μg/g and 42μg/g for Pyrene, and 21μg/g and 27μg/g for Benzo[a]Pyrene respectively. The maximum difference in removal rates between planted constructed wetland and unplanted constructed wetland was found to be 21% Phenanthrene, 13% Pyrene, and 30% Benzo[a]Pyrene. Both selected plants demonstrated high tolerance, uptake, and accumulation of PAHs in different proportions. The HSFCWs planted with Phragmites showed high removal capacity of PAHs than other HSFCWs. Under scanning electron microscopy some notable changes were observed in the internal composition of both plants. The mass balance calculations of the HSFCWs provided a clear picture of the key constructed wetland processes and helped to identify the components that are most important for PAHs treatment using HSFCW.